De novo variants in GATAD2A in individuals with a neurodevelopmental disorder: GATAD2A-related neurodevelopmental disorder - Elizabeth A. Werren; Alba Guxholli; Natasha Jones; Matias Wagner; Iris Hannibal; Jorge L. Granadillo; Amanda V. Tyndall; Amanda Moccia; Ryan Kuehl; Kristin M. Levandoski; Debra L. Day-Salvatore; Marsha Wheeler; et al. (HGG Advances, 2023)
Summary: GATA zinc finger domain containing 2A (GATAD2A) is a subunit of the nucleosome remodeling and deacetylase (NuRD) complex. NuRD is known to regulate gene expression during neural development and other processes. The NuRD complex modulates chromatin status through histone deacetylation and ATP-dependent chromatin remodeling activities. Several neurodevelopmental disorders (NDDs) have been previously linked to variants in other components of NuRD’s chromatin remodeling subcomplex (NuRDopathies). We identified five individuals with features of an NDD that possessed de novo autosomal dominant variants in GATAD2A. Core features in affected individuals include global developmental delay, structural brain defects, and craniofacial dysmorphology. These GATAD2A variants are predicted to affect protein dosage and/or interactions with other NuRD chromatin remodeling subunits. We provide evidence that a GATAD2A missense variant disrupts interactions of GATAD2A with CHD3, CHD4, and CHD5. Our findings expand the list of NuRDopathies and provide evidence that GATAD2A variants are the genetic basis of a previously uncharacterized developmental disorder.